PENGARUH PEMBERIAN KOMBINASI SHORT WAVE DIATHERMY DAN STRETCHING HAMSTRING TERHADAP PENINGKATAN KEMAMPUAN FUNGSIONAL PADA PASIEN OSTEOARTHRITIS KNEE UNILATERAL - Apriana Rahayuningsih; Fransisca Xaferia Hargiani; Rachma Putri Kasimbara; Nurul Halimah (Institut Teknologi, Sains, dan Kesehatan RS.DR. Soepraoen Kesdam V/BRW, 2024)
Introduction: Osteoarthritis of the knee is a degenerative joint disease that causes limited joint mobility. As a result, limited joint mobility can cause a decrease in the knee's functional ability. Hamstring stretching is a form of exercise that aims to stretch or stretch muscles that have decreased elasticity and flexibility, so it reduces scope limitations motion of the knee joint to repair the walking patterns in order to improve knee functional abilities. The purpose of this study is to determine the effect of giving a combination of short-wave diathermy and stretching toward improving functional abilities in osteoarthritis knee unilateral patients. Methods: This type of research uses quasi-experiments with one group pretest and posttest design methods. With a population of 30 people taken randomly. It uses the Womac scale measuring instrument with a combination exercise design of short-wave diathermy and hamstring stretching which is given 2 times a week for one month. Results: Wilcoxon hypothesis test obtained a median value pre 47.00 and post 44.00 with a difference of 3.00, p-value=0.000 (p <0.005). Conclusion: there is an effect of giving a combination of short-wave diathermy and hamstring stretching for 8 treatments on functional improvement in unilateral knee osteoarthritis conditions. Keywords: knee osteoarthritis, short wave diathermy, stretching hamstring